2013
DOI: 10.1007/s10198-013-0531-y
|View full text |Cite
|
Sign up to set email alerts
|

The link between past informal payments and willingness of the Hungarian population to pay formal fees for health care services: results from a contingent valuation study

Abstract: We examine the willingness of health care consumers to pay formal fees for health care use and how this willingness to pay is associated with past informal payments. We use data from a survey carried out in Hungary in 2010 among a representative sample of 1,037 respondents. The contingent valuation method is used to elicit the willingness to pay official charges for health care services covered by the social health insurance if certain quality attributes (regarding the health care facility, access to the servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 30 publications
0
15
0
3
Order By: Relevance
“…Some studies have reported a meaningful relationship between informal payment behavior with gender, age, educational level, place of residence, health insurance coverage and household economic status (6,13,22,(38)(39)(40)(41)(42). This discrepancy in the results can be attributed to the study setting (hospi- tal or household), the type of surveyed patients, country of study, and the data analysis methods.…”
Section: Discussionmentioning
confidence: 45%
“…Some studies have reported a meaningful relationship between informal payment behavior with gender, age, educational level, place of residence, health insurance coverage and household economic status (6,13,22,(38)(39)(40)(41)(42). This discrepancy in the results can be attributed to the study setting (hospi- tal or household), the type of surveyed patients, country of study, and the data analysis methods.…”
Section: Discussionmentioning
confidence: 45%
“…Among 38 reviewed studies,25 have assessed informal payment in 18 countries. It should be noted that some studies have evaluated prevalence only in the form of cash or gift.…”
mentioning
confidence: 99%
“…Így összevetve jelen eredményeinkkel, elmondható, hogy a két évvel korábbi felméréshez képest nőtt a családorvos-rezidensek körében a hálapénzt elutasítók aránya (50% vs. 38,3%) [27]. Vizsgálati eredményeinket árnyalja, hogy a "hálapénz-problémában" nem a családorvoslás a leginkább érintett ágazat: mind a nemzetközi, mind pedig a hazai vizsgála-tok kimutatták, hogy a fekvőbeteg-ellátás a legjobban érintett terület [4,5,[28][29][30], így eredményeink nem ál-talánosíthatóak más szakmákra, szakterületekre. A Markusovszky-ösztöndíj megléte is finomíthatja eredménye-inket: ezen ösztönző minden bizonnyal enyhíti a fiatal orvosgeneráció financiális nehézségeit, és elviekben szigorú tiltás alá vonja a hálapénz elfogadásának gyakorlatát.…”
Section: áBraunclassified